El ojo de jade - Liang, Diane Wei, 1966- (Nuevos tiempos (Madrid, Spain), 2010)
A tale set in modern Beijing follows a detective's search for a missing artifact, in a case that illuminates less-favorable aspects of Chinese culture and the detective's own family during the Cultural Revolution.